480 MHz 10-tap Clock Generator Using Edge-Combiner DLL for USB 2.0 Applications. (23rd January 2012) - Kawamoto, Takashi; Ueda, Kazuhiro; Noto, Takayuki
Abstract : A clock generator with an edge-combiner DLL (ECDLL) has been developed for USB 2.0 applications. The clock generator generates 480 MHz 10-tap output signals from a 12 MHz reference signal and consists of three DLLs to shrink the design area so that it is smaller than a conventional one based on a PLL. Each DLL is applied to our proposed shot pulse reset technique to prevent from a harmonic lock and is applied to a voltage-controlled delay line (VCDL) with a trimming function to operate against any process voltage temperature (PVT) variations. A 90 nm CMOS process was used to fabricate our proposed clock generator. The 480 MHz 10-tap output signals satisfy the USB 2.0 specifications. A power consumption is less than 1.3 mW and a locking time is less than 3.5  μ s, which are far less than a conventional one, 10.0  μ s. The design area is 200 × 225   μ m, which is half that of the conventional one.